Pengaruh Media Audio Visual Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran IPA Kelas 5 SDN 176 Pekanbaru - Nadia Farhiza; Laili Rahmi; Leny Julia Lingga (Social Science Academic, 2023)
This study aims to determine whether there is an influence of audio-visual media on students' learning motivation in science subjects in grade 5 SDN 176 Pekanbaru. This research is a type of quasi-experimental research, with a non-equivalent control group research design. The population in this study were all 5th grade students at SDN 176 Pekanbaru. The sample of this research was students in grades 5A and 5B, totaling 66 students at SDN 176 Pekanbaru. Determination of the sample using purposive sampling technique. The results showed that from the results of calculating students' learning motivation data, it was obtained that sig (2-tailed) = 0.000, indicating that the level of sig (2-tailed) = 0.000 is below the sig value. 5% or (0.000 <0.05), so that Ho is rejected, Hi is accepted. This means that there is an effect of the use of audio-visual media on student motivation. Then, seen from the acquisition of the average value of students' learning motivation results, it shows that the average score of learning using audio-visual media is 88.21, which is higher than the average group of students who do not use audio-visual media, which is 75.48. Therefore, it can be concluded that the learning motivation obtained by groups of students who study using audio-visual media is better than groups of students who do not use audio-visual media